Durable remissions in TCF3-HLF positive acute lymphoblastic leukemia with blinatumomab and stem cell transplantation - Mouttet, Brice; Kunz, Joachim (Haematologica, 2019)
TCF3-HLF -positive leukemia represents a rare subtype of childhood acute lymphoblastic leukemia (ALL), characterized by a high rate of treatment failure despite treatment intensification and allogeneic stem cell transplantation (SCT). Given the high and homogeneous expression of CD19 on blast cells